GC-MS Analysis and Cytotoxicity Evaluation of Shammah (Smokeless Tobacco) Samples of Jazan Region of Saudi Arabia as Promoter of Cancer Cell Proliferation - Asaad Khalid; Hassan A. Alhazmi; Ashraf N. Abdalla; Waquar Ahsan; Shahnaz Sultana; Mohammed Al Bratty; Sadique A. Javed; Zia ur Rehman (Journal of Chemistry)
Shammah is a locally manufactured form of smokeless tobacco (ST) which is traditionally used in Middle Eastern countries including Saudi Arabia, Sudan, and Yemen. Presence of a high concentration of nicotine, in addition to various other toxic and carcinogenic constituents, makes it a serious human health threat. It is an admixture containing powdered tobacco, along with several additives, such as lime, ash, black pepper, volatile oils, and flavoring agents. This study was conducted to investigate the constituents of eight different samples of widely used shammah varieties in the Jazan region of Saudi Arabia using GC-MS and to evaluate their cytotoxic effect against three cancer cell lines representing most of the top malignancies in the region including MCF-7, A2780, and HT29 cancer cells, in addition to MRC5 cells (normal human fetal lung fibroblast) using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. GC-MS analysis showed the presence of nicotine or 3-(1-methyl-2-pyrrolidinyl)pyridine (2.1–91.9% of total constituents detected) in all ST samples, whereas its derivative (1s,2s)-nicotine-N-oxide (0.23–1.62%) was detected in four samples. In addition, several known carcinogenic constituents were also identified, and their carcinogenicity was confirmed by MTT results, in which, all the eight samples promoted the growth of MCF7, A2780, and HT29 cancer cells. The cytotoxic effects of samples against the normal cells MRC5 was proportional to the number of components detected by GC-MS. The ingestion of these constituents through saliva of shammah consumers could be the reason for many cancers including breast, ovary, and colon cancers. These results support the urgent local and international call to educate the users regarding the deleterious effects of shammah to avoid its use.